Aufbau und Anwendung des FAL-Modellverbunds fur̈ die Politikberatung - Marcus Bertelsmeier; Werner Kleinhanss; Frank Offermann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2003)
– Structure and Application of the FAL's Economic Modelling Group for Policy AssessmentThe FAL model group combines several market, regional and farm models for comprehensive policy impact assessments. Since 1996, policy impact analyses have been provided at the request of the German Agricultural Ministry with respect to the design of direct payments, the Agenda 2000, the Mid-term Review, the Enlargement of the EU as well as several other policy measures. This article gives an overview of the models available as part of the model group, specifically describes the design of the representative farm group model, and provides results with respect to the impacts of the Mid-term Review. The paper ends with a discussion of the experiences gained in model based policy consulting and the implications for future developments.
Keywords: 330; Landwirtschaft; Politikberatung; Agrarpolitik; Deutschland